Renovation nation our obsession with home - Allon, Fiona R. (New South, 2008)
"This is an intelligent, savvy account of home in all its manifestations. It's about our fetish for home and ownership. Why are Australians so obsessed with interest rates, home ownership, home beautification, investment properties, real estate? Fiona Allon looks at our own homes--why we renovate, why shows like The Block were so incredibly popular, why housing affordability has become one of the key political and social issues--and finds that we have become more inward looking than ever. She also looks at the national 'home', and at why we became so anxious about keeping some people out of the country, or away from places some thought they owned, like Cronulla Beach."--Provided by publisher.